Nuevos registros de distribución para gallareta andina (Fulica ardesiaca), pato puneño (Anas puna), pato zambullidor grande (Oxyura ferruginea) y cuervillo puneño (Plegadis ridgwayi), en el embalse La Angostura, Tafí del Valle, Tucumán - Echevarria, Ada L.; Chani, José M.; Marano, Claudia F.; Cocimano, M. Constanza (Acta Zoológica Lilloana, 2008)
Distribution records for four species of birds are reported from studies carried out between 2004 and 2005 at La Angostura Dam (26º55’S, 65º41’W). The species are known to inhabit lakes, lagoons, pools, marshes and streams, generally above 3000 m. Here they are found at a lower elevation, circa 2000 m. They are Fulica ardesiaca (American Coot), present all year, with high abundance and continuous nest building records; Anas puna (Puna Teal), observed in the area during winter; Oxyura ferruginea (Andean Ruddy Duck), present throughout the year, with greater abundance in winter, and Plegadis ridgwayi (Puna Ibis), with a few individuals observed in summer, autumn and winter.